Respuesta :
Answer:
2√2 / (5√2 + 7)
Step-by-step explanation:
Given :
- x = 1 + √2
Expanding
- (x - 1 / x)³
- (1 + √2 - 1)³ / (1 + √2)³
- (√2)³ / (1 + √2)³
- 2√2 / 1 + 2√2 + 3(1)(√2)(1 + √2)
- 2√2 / 1 + 2√2 + 3√2 + 6
- 2√2 / (5√2 + 7)
Answer:
[tex]-14\sqrt{2}+20[/tex]
Step-by-step explanation:
[tex]\textsf{Substituting}\quad x=1+\sqrt2\quad\textsf{into}\quad\left(\dfrac{x-1}{x}\right)^3[/tex]
[tex]\implies \left(\dfrac{(1+\sqrt2)-1}{(1+\sqrt2)}\right)^3[/tex]
[tex]\implies \left(\dfrac{\sqrt2}{1+\sqrt2}\right)^3[/tex]
[tex]\textsf{Apply exponent rule}:\left(\dfrac{a}{b}\right)^n=\dfrac{a^n}{b^n}[/tex]
[tex]\implies \dfrac{(\sqrt2)^3}{(1+\sqrt2)^3}[/tex]
Expand numerator:
[tex](\sqrt{2} )^3=\sqrt{2}\sqrt{2}\sqrt{2}=2\sqrt{2}[/tex]
Expand denominator:
[tex]\begin{aligned}(1+\sqrt2)^3 & = (1+\sqrt2)(1+\sqrt2)(1+\sqrt2)\\ & =(1+\sqrt2)(1+2\sqrt{2}+2)\\ & =1+2\sqrt{2}+2+\sqrt{2}+2\sqrt{2}\sqrt{2}+2\sqrt{2}\\ & = 7+5\sqrt{2}\end{aligned}[/tex]
[tex]\implies \dfrac{(\sqrt2)^3}{7+5\sqrt2}[/tex]
Substituting expanded numerator and denominator:
[tex]\implies \dfrac{2\sqrt{2}}{7+5\sqrt2}[/tex]
[tex]\textsf{Mulitply by conjugate :}\quad\dfrac{7-5\sqrt2}{7-5\sqrt2}[/tex]
[tex]\implies \dfrac{2\sqrt{2}(7-5\sqrt2)}{(7+5\sqrt2)(7-5\sqrt2)}[/tex]
[tex]\implies \dfrac{14\sqrt{2}-20}{49-50}[/tex]
[tex]\implies \dfrac{14\sqrt{2}-20}{-1}[/tex]
[tex]\implies -14\sqrt{2}+20[/tex]